Construction of TiO2/starch nanocomposite cryogel for ethylene removal and banana preservation. (15th July 2023) - Xu, Jieru; Wang, Fan; Zhan, Jinling; Li, Yu; Wang, Tong; Ma, Rongrong; Tian, Yaoqi
Abstract: Perishability caused by natural plant hormone ethylene has attracted great attention in the field of fruit and vegetable (F&V) preservation. Various physical and chemical methods have been applied to remove ethylene, but the eco-unfriendliness and toxicity of these methods limit their application. Herein, a novel starch-based ethylene scavenger was developed by introducing TiO2 nanoparticles into starch cryogel and applying ultrasonic treatment to further improve ethylene removal efficiency. As a porous carrier, the pore wall of cryogel provided dispersion space, which increased the area of TiO2 exposed to UV light, thereby endowing starch cryogel with ethylene removal capacity. The photocatalytic performance of scavenger reached the maximum ethylene degradation efficiency of 89.60 % when the TiO2 loading was 3 %. Ultrasonic treatment interrupted starch molecular chains and then promoted their rearrangement, increasing the material specific surface area from 54.6 m 2 /g to 225.15 m 2 /g and improving the ethylene degradation efficiency by 63.23 % compared with the non-sonicated cryogel. Furthermore, the scavenger exhibits good practicability for removing ethylene as a banana package. This work provides a new carbohydrate-based ethylene scavenger, utilizing as a non-food contact inner filler of F&V packaging in practical applications, which exhibits great potential in F&V preservation and broadens the application fields of starch. Graphical abstract: Unlabelled Image